2015
DOI: 10.1007/s10086-015-1469-8
|View full text |Cite
|
Sign up to set email alerts
|

Strength of bolted timber joints subjected to lateral force

Abstract: The safety and serviceability of timber structures are frequently governed by the performance of joints. Bolted joints are a very commonly used form of joints and are effective from the viewpoint of the load-slip characteristics when subjected to a lateral force. The shear strength of a bolted joint is affected by various factors. Some of the factors affecting the shear strength of a bolted joint are classified into four categories in this paper: the material characteristics, geometrical factors, assembly cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…1 College of Agriculture, Academic Institute, Shizuoka University, 836 Ohya, Suruga-ku, Shizuoka 422-8529, Japan. 2 Industrial Research Center, Aichi Center for Industry and Science Technology, 1-157-1, Onda-cho, Kariya, Aichi 448-0013, Japan.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 College of Agriculture, Academic Institute, Shizuoka University, 836 Ohya, Suruga-ku, Shizuoka 422-8529, Japan. 2 Industrial Research Center, Aichi Center for Industry and Science Technology, 1-157-1, Onda-cho, Kariya, Aichi 448-0013, Japan.…”
Section: Fundingmentioning
confidence: 99%
“…Therefore, it is necessary to understand the lateral resistance of these joints. Consequently, many studies have been conducted, and a review of such studies has been reported by Sawata [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The authors declare that they have no competing interests. 1 Tokyo Metropolitan Industrial Technology Research Institute, 2-4-10, Aomi, Koto-Ku, Tokyo 135-0064, Japan. 2 Toyama Prefectural Agricultural, Forestry…”
Section: Fundingmentioning
confidence: 99%
“…Bolted joints are the most common type of joining method utilized in wooden structures [1]. Bolted joints are tightened with a nut during their installation, however, the force generated (initial tightening force) cannot hold up in the long term due to stress relaxation of the wood [2].…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness of connections is closely related to the physical and mechanical properties of timber and fasteners [17,18], as well as to the design of individual details (i.e., placement of individual fasteners and the whole connection geometry) [19][20][21]. The influence of connection stiffness manifests in increased deformations and redistribution of internal forces, which can significantly affect the static design of the whole load-carrying structure [7].…”
Section: Introductionmentioning
confidence: 99%